Philosophical Reason and the Tradition of Faith: Thomas Aquinas on the Preambles of Faith - Velde, Rudi A. te (Proceedings of the American Catholic Philosophical Association, 2022)
Traditionally, the praeambula fidei form the place where philosophy enters the theological discourse on faith. The task of philosophy in this context is to argue for the truths about God that are presupposed by faith. In the literature, the preambles are often linked with the foundational project of natural theology with its focus on the question of God's existence. This article argues that the preambles actually concern the two preliminary questions of the science of faith, namely, the question whether God is and the question what God is. With these two questions, Aquinas seeks to establish the intelligible form of the reality of God, being the subject of theology.